Inspection and lifting and inspection equipment - Pasichny, V. (Запоріжжя : 2024, 2024)
EN: When performing maintenance and repair of vehicles, a significant proportion of work (40...45%) is performed from below, for which the workshops must be equipped with inspection and lifting and transport equipment. Inspection and lifting-inspection equipment includes equipment that provides convenient access to units, mechanisms and parts located below and on the side of the vehicle during its maintenance and repair. Maintenance and repair work performed from below the car can be carried out with full or partial hanging or without hanging the car. Inspection equipment includes ditches and overpasses. Inspection ditches (Fig. 6.2) are the most common using universal inspection devices in workshops. Depending on the method of driving a car into a ditch and leaving it, there are different There are dead-end and direct-flow ditches (passage ditches). By width, ditches are divided into narrow (inter-track) and wide, by design - into inter-track and side, with knee bridges and with hanging wheels, trench and isolated.
Keywords: maintenance; repair; lifting and transport equipment